Risk Evaluation of EMT and Inflammation in Metastatic Pancreatic Cancer Cells Following Plasma Treatment - Freund, Eric; Spadola, Chiara; Schmidt, Anke; Privat-Maldonado, Angela; Bogaerts, Annemie; von Woedtke, Thomas; Weltmann, Klaus-Dieter; Heidecke, Claus-Dieter; Partecke, Lars-Ivo; Käding, André; Bekeschus, Sander (Frontiers in Physics, 2020)
The requirements for new technologies to serve as anticancer agents go far beyond their toxicity potential. Novel applications also need to be safe on a molecular and patient level. In a broader sense, this also relates to cancer metastasis and inflammation. In a previous study, the toxicity of an atmospheric pressure argon plasma jet in four human pancreatic cancer cell lines was confirmed and plasma treatment did not promote metastasis in vitro and in ovo. Here, these results are extended by additional types of analysis and new models to validate and define on a molecular level the changes related to metastatic processes in pancreatic cancer cells following plasma treatment in vitro and in ovo. In solid tumors that were grown on the chorion-allantois membrane of fertilized chicken eggs (TUM-CAM), plasma treatment induced modest to profound apoptosis in the tissues. This, however, was not associated with a change in the expression levels of adhesion molecules, as shown using immunofluorescence of ultrathin tissue sections. Culturing of the cells detached from these solid tumors for 6d revealed a similar or smaller total growth area and expression of ZEB1, a transcription factor associated with cancer metastasis, in the plasma-treated pancreatic cancer tissues. Analysis of in vitro and in ovo supernatants of 13 different cytokines and chemokines revealed cell line-specific effects of the plasma treatment but a noticeable increase of, e.g., growth-promoting interleukin 10 was not observed. Moreover, markers of epithelial-to-mesenchymal transition (EMT), a metastasis-promoting cellular program, were investigated. Plasma-treated pancreatic cancer cells did not present an EMT-profile. Finally, a realistic 3D tumor spheroid co-culture model with pancreatic stellate cells was employed, and the invasive properties in a gel-like cellular matrix were investigated. Tumor outgrowth and spread was similar or decreased in the plasma conditions. Altogether, these results provide valuable insights into the effect of plasma treatment on metastasis-related properties of cancer cells and did not suggest EMT-promoting effects of this novel cancer therapy.